2016 IEEE International Symposium on Information Theory (ISIT) 2016
DOI: 10.1109/isit.2016.7541454
|View full text |Cite
|
Sign up to set email alerts
|

On the capacity of diffusion-based molecular timing channels

Abstract: This work introduces capacity limits for molecular timing (MT) channels, where information is modulated on the release timing of small information particles, and decoded from the time of arrival at the receiver. It is shown that the random time of arrival can be represented as an additive noise channel, and for the diffusion-based MT (DBMT) channel, this noise is distributed according to the Lévy distribution. Lower and upper bounds on the capacity of the DBMT channel are derived for the case where the delay a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 14 publications
0
57
0
Order By: Relevance
“…As part of future work, we will explore extending the results to the case where multiple information particles are released simultaneously instead of one. Note that some of our current ongoing work has shown that simultaneously releasing multiple particles can improve the performance of the first system significantly [24], [27]. We would like to extend these results to the asynchronous systems presented in this paper using order statistics.…”
Section: Discussionmentioning
confidence: 66%
“…As part of future work, we will explore extending the results to the case where multiple information particles are released simultaneously instead of one. Note that some of our current ongoing work has shown that simultaneously releasing multiple particles can improve the performance of the first system significantly [24], [27]. We would like to extend these results to the asynchronous systems presented in this paper using order statistics.…”
Section: Discussionmentioning
confidence: 66%
“…Based on this assumption, the elements in T dly are independent and identically distributed and assume only non-negative real values. For an unbounded 1D environment, the random observation delay follows a Levy distribution if no flow is present [97] and the inverse Gaussian distribution if flow in the direction of the receiver is present [95]. We note that, in practice, T arv is not available at the receiver since i) different molecules of the same type are indistinguishable by the receiver and ii) out of the total number of released molecules, only n arv (t) molecules are observed by time t. In fact, T arv (t) is the actual observation signal available to the receiver.…”
Section: A Unified Signal Definitionmentioning
confidence: 99%
“…We now ask: What is the range of τ where D FA ≥ D LA ? To answer this question we compare (12) and (21) and write:…”
Section: Comparing the Fa And La Detectorsmentioning
confidence: 99%
“…Next, we consider the truncated (clipped) Lévy and IG distributions. 2) The Truncated Lévy and IG Distributions: Considering the truncated Lévy and IG distributions is motivated by scenarios where the information particles degrade over time [21], [24]. Specifically, these truncated distributions model a finite lifespan of the particles, where the particles are dissipated immediately after the time interval [0, τ ].…”
Section: B Densities With τ < ∞mentioning
confidence: 99%